Berberine Sensitizes Human Hepatoma Cells to Regorafenib via Modulating Expression of Circular RNAs - Wang, Kunyuan; Yu, Ganxiang; Lin, Jiaen; Wang, Zhilei; Lu, Qianting; Gu, Chengxin; Yang, Tao; Liu, Shiming; Yang, Hui (Frontiers in Pharmacology, 2021)
Regorafenib resistance is a key limiting factor in the treatment of advanced hepatocellular carcinoma (HCC). Increasing evidence has demonstrated that Berberine (BBR) can synergistically enhance the therapeutic effect of various chemotherapeutic agents. However, the contribution of BBR on regorafenib therapy remains unclear. The purpose of this study was to explore the combined treatment effect of berberine and regorafenib in HCC. We found that BBR enhanced the cytotoxicity of regorafenib in HCC cells. Compared with regorafenib alone, the combined treatment of BBR and regorafenib significantly inhibited the proliferation of HCC cells and induced cellular apoptosis. Meanwhile, the combined treatment group with BBR (10mg/kg/day) and regorafenib (5mg/kg/day) had a dramatic inhibitory effect on the growth of HCC xenograft tumors in nude mice. The increased apoptosis of xenograft tumors was seen in the combined treatment group. Moreover, a comprehensive circular RNA sequencing was performed to identify differentially expressed circRNAs in HCC cells after exposure to 100µM BBR and 5µM regorafenib. The volcano plot and scatter plot analyses revealed that there were 58 up-regulated and 19 down-regulated diﬀerentially expressed circRNAs between the combination treatment and control groups. Among them, the expression of hsa_circ_0032029 and hsa_circ_0008928 were up-regulated in HCC cells after treatment with 100µM BBR and 5µM regorafenib. Taken together, this study demonstrated that BBR enhanced the anti-HCC effect of regorafenib both in vitro and in vivo. The synergistic anti-tumor effect of BBR and regorafenib might be related to the up-regulation of hsa_circ_0032029 and hsa_circ_0008928 in HCC cells.